New host association between the cuckoo wasp Caenochrysis striatidorsa (Linsenmaier, 1984) and mason wasp Pison plaumanni Menke, 1968 (Hymenoptera: Aculeata) - Silva, Paulo V. A.; Maciel, Tatiane T.; Brito, Samanta; Lucena, Daercio A. A.; Barbosa, Bruno C. (Entomological Communications, 2024)
This study reports a new association between Caenochrysis striatidorsa (Linsenmaier, 1984) (Hymenoptera, Shrysidinae) and Pison plaumanni Menke, 1968 (Hymenoptera: Crabronidae), aiming to expand the basic knowledge of these groups. Nests were collected between 2016 and 2017 in the states of Rio de Janeiro and Minas Gerais, and the distribution range of the species was also updated.